Multi-featured epoxy composites filled with surface-modified PTFE powders treated by Na-naphthalenide system - AKIN, EMRE; ÇAKIR, MUSTAFA; DEMİRER, HALİL (My University, 2023)
This study aimed to produce new multi-featured epoxy composites that are advanced in terms of mechanical properties, wear and impact resistance, and glass transition and heat deflection temperatures. Epoxy composites filled with chemically surface-treated poly (tetrafluoroethylene) (PTFE) powders at various ratios were prepared to obtain these improved properties. The chemical treatment was carried out via a Na-naphthalenide system. After this treatment, the x-ray photoelectron spectroscopy results presented the existence of functional groups such as OH, carbonyl groups, and C=C unsaturation points on the surface of the PTFE powders. On the PTFE surfaces, while the atomic ratios of carbon and oxygen were substantially increased, the fluorine ratio presented a significant decrease after the chemical treatment. However, the wear rates of the novel composites were highly advanced despite this large decrease in the fluorine ratio on the surface of the PTFE powders. Moreover, functional groups such as OH, carbonyl groups, and C=C unsaturation points and spongelike or network structures on the PTFE surfaces provided the opportunity to obtain strong adhesion and interfacial bonding between the surface-modified PTFE powders and the matrix. Strength and modulus values showed substantial enhancement besides the IZOD impact resistance. All glass transition and heat deflection temperatures were also substantially improved.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; POLİMER BİLİMİ; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; POLYMER SCIENCE; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya; Fizik Bilimleri; Yüzeyler, Kaplamalar ve Filmler; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Surfaces, Coatings and Films; Polymers and Plastics; Materials Chemistry; epoxy composite; Na-naphthalenide system; surface-modified PTFE particles